Low-metallicity CO + He WD post-merger models for RCB stars as a source of pre-solar graphite grains. Issue 2 (24th September 2018) - Menon, Athira; Karakas, Amanda I; Lugaro, Maria; Doherty, Carolyn L; Ritter, Christian
ABSTRACT: R Coronae Borealis (RCB) stars are predominantly metal-poor, near-solar mass hydrogen-deficient carbon-rich supergiants that have evolved from mergers of carbon–oxygen and helium white dwarf (WD) systems. They have some of the lowest 16 O/ 18 O ratios measured in any star (between 1 and 25) and are also enhanced compared to solar, in fluorine and the s-process elements. In the paper by Menon et al., post-WD-merger stellar evolution models of RCBs constructed at solar metallicity could reproduce the above chemical signatures. In this work, we construct new post-WD-merger models with a realistic RCB metallicity of [Fe/H] = −1.4, using the same methodology as Menon et al. An important aspect of this method was the inclusion of an artificial mixing process during the evolution of the models, which was essential to reproduce the isotopic ratios of RCBs. The surface of our new post-merger models have 16 O/ 18 O ratios of 9.5–30, 12 C/ 13 C ratios of 1500–7000 which overlap with the values recorded for RCBs, along with their enhancements in fluorine and in s-process elements. We then explore the possibility that a fraction of pre-solar low-density graphite grains, those with comparable   16 O/ 18 O and   12 C/ 13 C ratios as RCBs, were formed in the outflows of these stars. On assuming that the gas ejected by RCBs would have mixed with its surrounding interstellar material of solar composition, our models can reproduce some of the isotopic ratios of these graphite grains, thereby strengthening the hypothesis that RCB stars could be a source of some pre-solar graphite grains.